Análise da rugosidade superficial do esmalte humano exposto ou não à ação de agente clareador após escovação com diferentes dentifrícios - Pachaly, Raquel (2009)
The aim this study was to evaluate, in vitro, the average surface roughness (Ra) of human enamel exposed or not to the action of bleaching agent with carbamide peroxide (CP) 10% after brushing with different dentifrices. Ninety-six (96) specimen enamel was used and divided into two groups: GI- exposed to the action of bleaching agent and GII- non exposed to the action of bleaching agent and subdivided into eight subgroups of brushing: (CEW) Close-Up Extra Whitening, (CUB) Colgate Ultra White (CPC) Crest Cavity Protection and (DW) deionized water. The specimens from the GI group were submitted to the bleaching treatment with PC10% for 6h during14 days; the GII group were stored in artificial saliva for 14 days. After this period the groups were subjected to 35,600 cycles in the mechanical toothbrushing machine equivalent to 2 years and a half of the normal brushing, using the Oral-B toothbrush. The Ra was measured before and after brushing with Mitutoyo SJ 201P perfilometer. The results were submitted to ANOVA and Tukey test (5%) and indicated that there is not significant difference in Ra between GI and GII. Among the subgroups of brushing, it might be observed a significant increase of the roughness for the CEW subgroup with statistical difference for the CUB subgroup. The subgroups CCP and DW presented intermediate values of Ra not differing from the other subgroups of brushing. These results are related to different abrasives which are present in the composition of dentifrice once the abrasiveness of the dentifrice depend particle hardness, shape, size, size distribution and concentration.